The paradoxes of a countercolonial theatrical pedagogy (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This paper presents some anti-racist theater teaching methodologies developed and thought in the dialogue between teachers and students of university classes. To this end, there is a support in current epistemologies to propose a countercolonial theatrical pedagogy that focuses on the pedagogical and creative subjectivities of the class. Finally, the work presents contributions to think about a pedagogy of theater and its teaching methods in an expanded and countercolonial way.
Keywords: countercolonial; pedagogy of theatre; expanded pedagogy